Aesthetics and Human Resource Development : Connections, Concepts and Opportunities. (Taylor & Francis, 2005)
The first book to look at both aesthetics and human resource development, this timely and original work investigates existing, as well as possible future, connections and relations between the two areas. Well structured and expertly written, "The Aesthetic Challenges of Human Resource Development" is undoubtedly a valuable reference for students of human resource management, business and management, and aesthetics.